Effect of polydimethylsiloxane incorporation on the properties of polyimides synthesized from newly designed α,α'-bis(2-aminophenoxy)-p-xylene - A. R. Ashraf; Z. Akhter; V. McKee; M. Siddiq (eXPRESS Polymer Letters)
A novel diamine monomer α,α'-bis(2-aminophenoxy)-p-xylene (2APX) was synthesized and condensed with four different dianhydrides to prepare a series of polyimides. Aminopropyl terminated polydimethylsiloxane (PDMS) was incorporated within the backbone of polyimides for the preparation of poly(imide siloxane) copolymers. Fourier transform infrared (FTIR), 1H and 13C nuclear magnetic resonance (NMR) spectroscopic studies accompanied by elemental and single crystal X-ray analysis were performed for structure elucidation of 2NPX and 2APX. The crystal system of the 2NPX was found to be monoclinic, belonging to space group P21/n while 2APX was triclinic with space group P1. The structural elucidation of polymers was carried out by FTIR and 1H NMR spectroscopy and their properties were studied by solubility testing, wide angle X-ray diffraction (WAXRD), thermogravimetric analysis (TGA) and viscosity measurement along with laser light scattering technique (LLS). WAXRD pattern showed the semicrystalline nature of polyimides which was decreased in case of copolymers. The poly(imide siloxane) copolymers displayed slightly lower temperature resistance but improved solubility as compared to polyimides. Maximum degradation temperature (Tmax.) of polyimides was in the range of 523–570°C while that of copolyimides, ranged between 483–525°C. Similarly, a decline in inherent viscosities and increase in molecular weight was noticed while moving from polyimides to copolyimides.